2017
DOI: 10.1212/wnl.0000000000004153
|View full text |Cite
|
Sign up to set email alerts
|

Slowing gait and risk for cognitive impairment

Abstract: The association between gait slowing and cognitive impairment is supported by a shared neural substrate that includes a smaller right hippocampus. This finding underscores the value of long-term gait slowing as an early indicator of dementia risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 40 publications
9
57
1
1
Order By: Relevance
“…Participants are primarily white (93%, self-identified), matching South Island demographic characteristics. 9 Assessments were performed at birth; at ages 3,5,7,9,11,13,15,18,21,26,32, and 38 years; and, most recently (completed April 2019), at age 45 years, when 938 of the 997 participants (94.1%) still alive participated. At each assessment, each participant was brought to the research unit for interviews and examinations.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Participants are primarily white (93%, self-identified), matching South Island demographic characteristics. 9 Assessments were performed at birth; at ages 3,5,7,9,11,13,15,18,21,26,32, and 38 years; and, most recently (completed April 2019), at age 45 years, when 938 of the 997 participants (94.1%) still alive participated. At each assessment, each participant was brought to the research unit for interviews and examinations.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…While speed could be considered useful in clinical screening, other studies indicate that it is also important to establish how gait parameters would be involved in aging since it has been reported that they could predict the risk of falls and loss in mobility affecting the quality of life [11]. The importance of these findings lies in the recognition of predictive factors that are easily accessible to clinicians who can detect early cognitive deterioration as well as dementia, which in turn will enable the creation of better strategies for planning, prevention, and treatment options [12].…”
Section: Gait and Agingmentioning
confidence: 99%
“…Balance, muscle strength, gait and cognitive impairments all significantly increase the risk of falls [11][12][13]. Cognitive impairment compromises 'top down' control of gait and balance, which is required for navigating the environment [14,15]. People with dementia are eight times more likely to fall than those without dementia [16], and falls account for 26% of hospital admissions in those with dementia [17].…”
Section: Introductionmentioning
confidence: 99%